2010
DOI: 10.1002/clc.20839
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Quality of Care and Lifestyle Counseling Among Patients With Heart Disease

Abstract: Background: To examine patients' perceived quality of care and reported receipt of information on diet and exercise related to cardiovascular disease prevention. Methods: Patients admitted with acute coronary syndromes or elective cardiac catheterization were eligible for enrollment. Baseline medical information was collected through medical-record review. Patients completed surveys at the time of hospitalization that included items on perceived quality of care and whether they had received information from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Participants also mentioned the role of the media in positively affecting people's attitudes toward living a healthier lifestyle, specifically that media plays a role in being a good source of information. This is supported by Jackson et al, [31] whose survey of 182 cardiac patients showed that many patients get their health guidance from magazines and newspapers, and 25% of patients reported using the internet as a source of medical information. Participants in our study suggested that TV programs, advertisements in shopping malls, and attractive displays may increase public health awareness.…”
Section: Recommendations For Promoting Physical Activitymentioning
confidence: 72%
See 1 more Smart Citation
“…Participants also mentioned the role of the media in positively affecting people's attitudes toward living a healthier lifestyle, specifically that media plays a role in being a good source of information. This is supported by Jackson et al, [31] whose survey of 182 cardiac patients showed that many patients get their health guidance from magazines and newspapers, and 25% of patients reported using the internet as a source of medical information. Participants in our study suggested that TV programs, advertisements in shopping malls, and attractive displays may increase public health awareness.…”
Section: Recommendations For Promoting Physical Activitymentioning
confidence: 72%
“…Thus, counselling and guidance for patients by health care providers, especially physicians, regarding smoking cessation, weight loss, and exercise should be a key interventions to modify lifestyle behaviors among cardiac patients. [31] Some participants commented that at present, in Qatar, there are gymnasiums and recreational facilities that maintain privacy for females in order to encourage more exercise. The effect of this is supported by a study recommending that the design and implementation of a physical exercise regimen should be sensitive to cultural differences in modesty, assertiveness, and expected social roles.…”
Section: Recommendations For Promoting Physical Activitymentioning
confidence: 99%
“…Nonetheless, we argue that professional counseling and guidance, especially physicians’, regarding medical health, weight loss, and exercise can be a pivotal formal support to modify lifestyle behavior [ 25 , 56 ]. As one participant recommended, physicians can play an important role in prescribing physical activity to individual clients because many NCDs can be improved and prevented with lifestyle changes.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Health promotion activities focused on screening and addressing lifestyle behaviors including physical inactivity, poor diet, and smoking are now included in the clinical care guidelines for many disciplines, including occupational therapy (OT) and physical therapy (PT; American Physical Therapy Association, 2015; Jensen et al, 2014;Kris-Etherton et al, 2014;Lichtenstein et al, 2006;Scaffa, Van Slyke, & Brownson, 2008). A number of studies also report that patients are amenable to discussions of lifestyle behaviors initiated by their healthcare providers, and may report higher perceived quality of care when providers have these discussions with their patients (Jackson, Krishnan, Meccone, Ockene, & Rubenfire, 2010;Pool et al, 2014;Rose, Poynter, Anderson, Noar, & Conigliaro, 2013).…”
Section: Introductionmentioning
confidence: 99%